Identifying Students’ Understanding Levels and Sources of Misconceptions in Acid–Base Concepts Through a Five-Tier Diagnostic Test - Sari, Sandi Danar Cynthia; Ardi, Triyanto; Parameswary, Clara Shabrina; Widiastuti, Nabila Lailil (Department of Chemistr Education Faculty of Teacher Training and Education Universitas Su, 2025)
Identifying misconceptions experienced by students is an important step in understanding learning difficulties and designing more effective learning strategies. This study aims to analyze the level of understanding, misconceptions, and learning sources that cause students' misconceptions on acid-base material through the use of the Five-Tier Diagnostic Test. The results of the study show that 32.06% of students are in the sound understanding category, 25.44% in the partial understanding category, 7.21% have misconceptions, and 4.41% are in the not understanding category. The majority of students have understood the basic concepts of acids and bases, but many have only achieved partial understanding, which indicates partial comprehension without proper reasoning. Additionally, the analysis of the fifth tier, which identified the sources of misconceptions, revealed that 75.98% of misconceptions originated from personal thoughts, 14.95% from the internet, 9.06% from books, while teachers and other sources did not contribute (0.00%). The highest misconceptions were found in the subconcepts of pH and pOH, influenced by personal thoughts and daily experiences that do not align with scientific concepts. These findings confirm the effectiveness of the Five-Tier Diagnostic Test in revealing the details of students' understanding as well as the sources of misconceptions. Therefore, teachers need to utilize this instrument to design more targeted conceptual change-based learning strategies to reduce misconceptions in acid-base material.